2017
DOI: 10.33866/phytopathol.029.02.0404
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of New Chemistry Fungicides Against Charcoal Rot of Sesame Caused by Macrophomina Phasiolina in Pakistan

Abstract: The current research was conducted to find out the most appropriate concentrations of six fungicides for the management of sesame charcoal rot caused by Macrophomina phaseolina under lab and field conditions. The treatments viz. Antracol, Topsin-M, Mancozeb, Score, Topas, Nativo and Control with concentrations of 150, 250 and 350ppm were used with three replications under completely randomized design and randomized complete block design in Lab. and field conditions respectively. The mean colony growth of all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
(6 reference statements)
3
7
0
Order By: Relevance
“…The other isolates of F. solani and F. clmourum did not induce wilt symptoms, but they significantly caused the seedling damping-off. These results agree with those reported by Bashir et al (2017) . Previous studies reported that the cultivation of certain preceding plants effectively controlled various plant diseases caused by soil-borne fungi, including Fusarium wilt of sesame ( Bashir et al, 2017 , El Kichaoui et al, 2017 , Assefa et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The other isolates of F. solani and F. clmourum did not induce wilt symptoms, but they significantly caused the seedling damping-off. These results agree with those reported by Bashir et al (2017) . Previous studies reported that the cultivation of certain preceding plants effectively controlled various plant diseases caused by soil-borne fungi, including Fusarium wilt of sesame ( Bashir et al, 2017 , El Kichaoui et al, 2017 , Assefa et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…These results agree with those reported by Bashir et al (2017) . Previous studies reported that the cultivation of certain preceding plants effectively controlled various plant diseases caused by soil-borne fungi, including Fusarium wilt of sesame ( Bashir et al, 2017 , El Kichaoui et al, 2017 , Assefa et al, 2020 ). The lowest pre and/or post damping-off and wilt of sesame caused by F. oxysporum were recorded in plots where onion and garlic were cultivated, followed by wheat compared to clover in both the clover 2019 and 2020 seasons.…”
Section: Discussionsupporting
confidence: 94%
“…Our results showed that Nativo expressed least mycelial growth and highest inhibition percentage @ 6mM; 73.82 % at 7 th day as compared to the control. The results of this study are in line with the research of Bashir et al, (2017) who tested six different fungicides (Mancozeb, Topas, Topsin-M, Antracol, Score and Nativo @ 150, 250 and 350ppm) for their effectiveness against M. phaseolina under laboratory conditions and observed that Nativo showed significant results with reduction in the colony growth to a larger extent as compared to other fungicides tested. The results reported by Kumar et al, (2016) are also supportive to present study, the authors tested four concentrations (5, 10, 15 and 25 ppm) of Tebuconazole 50% + Trifloxystrobin 25% for the management of charcoal rot pathogen (M. phaseolina).…”
Section: Discussionsupporting
confidence: 89%
“…Last, the AS dosages and application method should be set and optimized to ensure minimal use and maximum impact. Similarly, other effective chemical compounds ( Bashir et al., 2017 ; Iqbal and Mukhtar, 2020b ) should be tested for the integrated control interphase to expand our options to restrict M. phaseolina damages. Studying the influence of the control methods presented here on other cotton soil diseases and other crops is also an intriguing and valuable future perspective.…”
Section: Discussionmentioning
confidence: 99%